Concave Urinary Crystallines: Direct Evidence of Calcium Oxalate Crystals Dissolution by Citrate In Vivo. (18th November 2013) - Shang, Yun-Feng; Xu, Meng; Zhang, Guang-Na; Ouyang, Jian-Ming
Abstract : The changes in urinary crystal properties in patients with calcium oxalate (CaOx) calculi after oral administration of potassium citrate (K3 cit) were investigated via atomic force microscopy (AFM), scanning electron microscopy (SEM), X-ray powder diffractometry (XRD), and zeta potential analyzer. The AFM and SEM results showed that the surface of urinary crystals became concave, the edges and corners of crystals became blunt, the average size of urinary crystallines decreased significantly, and aggregation of urinary crystals was reduced. These changes were attributed to the significant increase in concentration of excreted citrate to 492 ± 118  mg/L after K3 cit intake from 289 ± 83  mg/L before K3 cit intake. After the amount of urinary citrate was increased, it complexed with Ca 2+ ions on urinary crystals, which dissolved these crystals. Thus, the appearance of concave urinary crystals was a direct evidence of CaOx dissolution by citrate in vivo . The XRD results showed that the quantities and species of urinary crystals decreased after K3 cit intake. The mechanism of inhibition of formation of CaOx stones by K3 cit was possibly due to the complexation of Ca 2+ with citrate, increase in urine pH, concentration of urinary inhibitor glycosaminoglycans (GAGs), and the absolute value of zeta potential after K3 cit intake.